Cooperative Spectrum Sensing with Beamforming in Cognitive Radio Networks - Gang Xiong; Kishore, S (IEEE communications letters, 2011)
This letter presents a cooperative spectrum sensing scheme with beamforming for cognitive radio networks. Here, secondary users report spectrum measurements to a fusion center simultaneously with assigned beamforming weights. Under correlated log-normal shadowing, optimal beamforming weights are derived to maximize the global detection probability subject to a global transmit power constraint. Global detection performance with optimal beamforming weights is then evaluated. The analysis is tested on a linear, equi-distant network where secondary users have identical channel gains to the fusion center. Results show that more secondary users improve detection performance.